PENDEKATAN PEMBELAJARAN BERDIFERENSIASI DALAM MATA PELAJARAN IPAS: STUDI PADA KELAS IV SEKOLAH DASAR - Selly Ningsyih; Umil Muhsinin; Ika Panggih Wahyuningtyas (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study seeks to delineate the planning, execution, and assessment of a differentiated learning strategy in Natural and Social Sciences (IPAS) topics for grade IV at SD Negeri 004/VII Sarolangun Kembang I. The research employs a descriptive qualitative methodology with a field research design. Data gathering methods included observation, interviews, and recording including the principal, fourth-grade instructors, and students as primary data sources. Data analysis was conducted via data reduction, data presentation, and conclusion formulation. The study's findings reveal that educators have used differentiated learning using diagnostic evaluations to ascertain students' learning readiness, interests, and profiles. Teachers execute differentiation of content, processes, and results by modifying techniques, media, and learning activities based on student characteristics. Assessment is conducted continually via formative and summative evaluations to track student learning advancement. The use of differentiated learning fosters a more dynamic, inclusive, and student-centered educational environment. This research is distinguished by its comprehensive examination of the use of differentiated learning in scientific topics within the framework of the Independent Curriculum in primary schools, particularly regarding the planning, execution, and assessment of learning.